PRE-SERVICE TEACHER EDUCATORS ASSESSMENT OF ADEQUACY OF GOOGLE CLASSROOM APPLICATION AS TEACHING TOOLS IN TEACHER EDUCATION PROGRAMME, NIGERIA - Bello Bolanle Muhinat (Universitas Ahmad Dahlan, 2021)
Despite the increasing number of technologies and levels of educational technology provided by teacher education programmes, valid and high-level integration of technology into learning and teaching processes is not still as expected, like theÂ Google classroom for learning. The study purposively investigated the adequacy of Google classroom application as a teaching tool in the training of pre-service teachers by their educators. Three specific purposes and questions were raised. The study adopted a descriptive survey design. Pre-service teacher educators of the Faculty of Education, University of Ilorin constituted the target population. A simple random sampling procedure was adopted in the selection of 107 out of 197 Pre-service educators. A -14 item five-point-Likert scale researchers designed a questionnaire with psychometric properties of content validity of 0.90 and a reliability index of 0.81 was used to elicit the needed data from the respondents. The statistics collected were analysed using percentage, mean ranking and standard deviation. Moreover, the findings among others revealed that Google classroom application is not adequate for training pre-service teachers. Thus, it was recommended that Google classroom application should not be adopted in the teaching of pre-service teachersâ€™ education programme since it was found not adequate